A whole-system approach to improving the health and well-being of healthcare workers: a systematic review - Abdullah Al-Shami Al-Yahwi, Salem Muqbil Abdullah Al-Zahrani, Muhammad Jabr Al-Sulami, Talib Mohsen Alyoubi, Ahmad Jazaa Alharbi, Ahmed Thabit Alawi, Yahya Obedullah Alsobhi, Yousef Mubti Almarwani (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Work-related stress is considered the primary occupational health issue in the United Kingdom (UK), following musculoskeletal illnesses like back issues. The cost of stress-correlated sickness absences & musculoskeletal illnesses is estimated to be around £4 billion per year.Aim and objective: To determine whether healthy workplace interventions incorporating components of this whole system approach enhance the health & well-being of healthcare personnel & promote healthier behaviors, the objective is to identify such interventions in health care settings.Patients and methods: This systematic review includes human RCTs that were published in English. In addition, we examined the reference lists of the clinical investigations we involved & prior reviews by manual to identify any additional studies. MeSH & text keywords associated with "whole-system approach to improving the health & well-being of healthcare workers" were utilized by two authors in an independent search of online databases involving EMBASE, Scopus MEDLINE, Cochrane Library, & Web of Science.Results: The current study exhibited notable enhancements in all evaluated health behaviors, except for moderate exercise duration, healthy commuting, smoking frequency, & depressive symptoms. The intervention produced favorable outcomes for the individuals. By implementing enhancements to existing procedures.Conclusion: The present study offers evidence that whole workplace interventions aimed at promoting health and well-being can enhance the overall health & wellness of healthcare personnel and encourage the use of healthier behaviors.